A CONCEPTUAL FRAMEWORK OF ADVERTISING CREATIVITY DIMENSIONS AND THEIR IMPACT ON SALES PERFORMANCE AND CUSTOMER LOYALTY - Rosli, Nuraina Nadiah; Saleh, Nur Fathia; Amram, Nor Razuana; Hashim, Muhammad Asyraaf; Shariff, Qatrunnisa; Awang Besar, Nazirul Mubin (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
In the fast-paced fashion industry, a great advertisement must do more than just turn heads, it has to move the needle on sales and build lasting customer relationships. While the importance of creativity is well-recognized, there is still a missing link in understanding how originality, visual style, emotion, and clarity work together to impact a company’s bottom line. This study bridges that gap by developing a framework that treats creative advertising as a powerful spark for consumer connection. By blending the Stimulus-Organism-Response (S-O-R) model with Brand Equity Theory, the research shows how specific creative triggers shift a consumer’s mindset. When the right mix of aesthetic and emotional elements hits home, it builds the kind of brand equity that translates into higher purchase rates and genuine brand loyalty. Beyond the theory, this framework serves as a practical blueprint for marketers. It helps teams balance the "art" of a campaign with the "message," ensuring every creative choice serves a strategic business goal. By connecting creative stimuli directly to firm-level outcomes, the study invites future exploration into how these pillars hold up across the ever-evolving digital and traditional media landscapes.